2021
DOI: 10.1037/sgd0000433
|View full text |Cite
|
Sign up to set email alerts
|

The role of moral reasoning and attitudes regarding bisexuality in the development of bisexual counseling competence.

Abstract: Research on counselor competence regarding bisexuality is scarce, despite the greater prevalence of negative attitudes about bisexuality as compared to other sexual minorities (Flanders & Hatfield, 2014) both within the general public and the LGBTQ + community (Matsick & Rubin, 2018). Therapist attitudes and moral development are 2 constructs known to affect multicultural counseling competence; however, although some research has examined competence in working with lesbian, gay, and bisexual individuals altoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 58 publications
(141 reference statements)
1
13
0
Order By: Relevance
“…However, the unfortunate reality is that even though these ideals have been clarified and disseminated, translating them into action can be difficult. Recently, Wilcox et al (2020) and Monceaux et al (2021) found that despite widespread, codified expectations for multicultural training, therapists did not attend adequately to cultural factors in case conceptualization or at times did so in inappropriate or stigmatizing ways. There is a tension that exists between the push for culturally driven intervention and formulation and the historical influence of the monolithic, dominant culture on the field of psychology as a whole.…”
mentioning
confidence: 99%
“…However, the unfortunate reality is that even though these ideals have been clarified and disseminated, translating them into action can be difficult. Recently, Wilcox et al (2020) and Monceaux et al (2021) found that despite widespread, codified expectations for multicultural training, therapists did not attend adequately to cultural factors in case conceptualization or at times did so in inappropriate or stigmatizing ways. There is a tension that exists between the push for culturally driven intervention and formulation and the historical influence of the monolithic, dominant culture on the field of psychology as a whole.…”
mentioning
confidence: 99%
“…As well, it is possible that colorblind racial attitudes do not serve as a useful criterion variable from multicultural training, or at least multicultural training as measured in the present study. As for the MCKAS, scholars have questioned whether self-report multicultural competence measures are measuring competence per se, or rather, self-efficacy (e.g., Constantine, 2000; Constantine et al, 2002; Lantz et al, 2020; Wilcox et al, 2020), and have noted that participants tend to rate themselves highly on self-report measures, even despite limited integration of cultural variables into case conceptualization (Lantz et al, 2020; Monceaux et al, 2020; Wilcox et al, 2020). Thus, self-report measures may not adequately capture participants’ multicultural knowledge, awareness, and skills as originally intended.…”
Section: Discussionmentioning
confidence: 99%
“…Due to researchers highlighting a ceiling effect on MCC self-report measures, this is concerning (e.g., Lantz et al, 2020;Wilcox et al, 2020). Recent research (e.g., Monceaux et al, 2021;Wilcox et al, 2020) has sought to extend inquiry into cultural responsiveness by examining performancebased measures of MCC, specifically, case conceptualization.…”
Section: Therapist Cultural Responsivenessmentioning
confidence: 99%
“…Lantz et al (2020) found therapists higher in social dominance orientation self-reported lower multicultural awareness and knowledge; therapists, and psychology as an institution, are inherently rooted in HEREFORD, WILCOX, AND POLLARD dominant culture, rugged individualism, and the myth of meritocracy. This may explain why researchers have recently found that therapists do not appropriately address cultural factors in vignette studies focusing on conceptualization (Monceaux et al, 2021;Wilcox et al, 2020).…”
Section: Case Conceptualizationmentioning
confidence: 99%
See 1 more Smart Citation